HUBUNGAN POLA ASUH ORANG TUA DENGAN MOTIVASI ANAK DALAM BELAJAR DARING - Widhiastuti, Ratna; Hanum, Nur Kholida; Widyantoro, Wisnu (Jurnal EDUNursing, 2024)
The right parenting style will affect the high motivation in student learning activities, so that the use of online facilities can be applied maximally. One of the factors that influence learning motivation is the learning environment and parenting patterns which will then determine the learning quality of students. This research uses descriptive correlation with cross sectional approach. Sampling using simple total sampling technique, with a sample of 34 respondents. Data collection techniques using a questionnaire. Data processing using bivariate analysis with Kendall tau correlation technique, is declared significant if the p value <0.05. The results of the study found that authoritarian parenting (52.9%) with a low level of online learning motivation (32.4%). The results of statistical tests obtained p value = 0.00 which means p <0.05 and it can be concluded that parenting patterns with children's motivation in online learning in mentally retarded children have a relationship. Based on this research, it is hoped that it can become the basis for parenting with the level of motivation in mentally retarded children. Keywords: Parenting, Children with mental retardation, Motivation to learn online